Functional cookies formulation based on red ginger by- products (juice) for diabetes mellitus patients: approach zero waste in Micro, Small Medium Enterprise (MSMEs) - Isti Istianah; Ratnayani Ratnayani; Mia Srimiati; Ni'ma Ghaida; Meyra Sakura; Sarah Salsabila (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
Diabetes mellitus is one of the major health issues in Indonesia, and Diabetes mellitus is a significant health issue in Indonesia, and consuming low-glycemic index foods can help manage blood sugar levels. This study aimed to develop a cookie formula incorporating red ginger by-products and analyze its proximate composition, fiber content, antioxidant activity, and glycemic index. The research methods included an organoleptic test involving 30 panelists, chemical composition analysis, and a glycemic index test on 20 subjects. Organoleptic test results showed that cookies with red ginger by-products had a more preferred color and taste than control cookies. Chemical analysis revealed an increase in dietary fiber content and antioxidant activity in cookies containing red ginger byproducts. The glycemic index test indicated that these cookies contributed to a more stable reduction in the blood sugar levels. The study concludes that incorporating red ginger by-products into cookie formulations can provide additional nutritional benefits for patients with diabetes mellitus while supporting sustainability through a zero-waste approach. These findings highlight the potential of red ginger by-products as a functional food ingredient that benefits both health and environmental sustainability, encouraging further exploration of food by-product utilization in functional food development.